‘All that glitters is not Roman’ - Roman coins discovered in East Java, Indonesia: A study on new data with an overview on other coins discovered beyond India - Hoppál, Krisztina; Vida, István; Adhityatama, Shinatria; Yahui, Lu (Dissertationes Archaeologicae, 2019)
Studying extra regional trade networks in Antiquity can be considered a relatively popular field of research, but the intensity and patterns of such complex system still leave lot of questions, particularly in the case of Rome’s Far Eastern trade. There is still a trend to visualize a kind of globalized commercial activity between the Imperium and communities on the eastern edge of the Silk Road(s). However, the facts provide us a more comprehensive picture. Due to the meticulous work of international joint research projects working in East and Southeast Asia followed by a raised interest in collecting ancient objects among local people, an increasing number of Roman objects have been discovered in the region. These finds prove the significance of mediator cultures in transferring Roman artifacts beyond India – with their own imprints on forming evaluation/acceptance of these non-local goods by the receiving culture.